Evaluation of hematological and biochemical factors of hypertension during the induction chemotherapy for childhood acute lymphoblastic leukemia - Saha, Mousumi; Jamal, Chowdhury Yakub; Soma, Shahinoor Akter; Kaes, M. Imrul (International Journal of Contemporary Pediatrics, 2023)
Background: Acute lymphoblastic leukemia (ALL) is a prevalent childhood cancer, accounting for approximately 25% of all pediatric cancer cases. The incidence of hypertension in ALL patients is significantly higher compared to the general pediatric population, emphasizing the need for a better understanding and management of this condition. The aim of the study was to evaluate hematological and biochemical factors of hypertension during the induction of chemotherapy for childhood ALL. Methods: This prospective observational study was conducted in the Department of Pediatric Hematology and Oncology at BSMMU from July 2017 to June 2018. The study included 93 newly diagnosed cases of ALL in children aged 1 to 17.9 years, excluding those below 1 year and above 18 years, known cases of hypertension, patients with pre-existing hypertension before chemotherapy, and old or relapse cases of ALL. Results: The study found that 17.2% of the study population experienced renal derangement during the induction remission phase, while the majority (82.8%) did not. The presence of renal derangement was not significantly associated with hypertension. However, patients who developed tumor lysis syndrome (TLS) had a higher percentage (12.5%) of hypertension compared to the non-hypertensive group (1.3%). Febrile neutropenia, convulsion, and coagulopathy were also observed in patients who developed hypertension more frequently. The median time to detect hypertension during induction chemotherapy was on day 8, with a mean duration of 13.6 days. Conclusions: In this study, hypertension is observed in 17.2% of patients during induction chemotherapy for ALL with higher frequency in the second week and associations with tumor lysis syndrome, febrile neutropenia, convulsion, and coagulopathy.